2020
DOI: 10.3389/fonc.2020.00375
|View full text |Cite
|
Sign up to set email alerts
|

BCL11A Promotes the Progression of Laryngeal Squamous Cell Carcinoma

Abstract: Background: We report functional and clinical data uncovering the significance of B-cell lymphoma/leukemia 11A (BCL11A) in laryngeal squamous cell carcinoma (LSCC). Methods: We examined BCL11A expression in a cohort of LSCC patients and evaluated the association between BCL11A expression and clinicopathological features. We investigated the consequences of overexpressing BCL11A in the LSCC cell line on proliferation, migration, invasion, cell cycle, chemosensitivity, and growth in vivo. We explored the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Besides, by directly interacting with the 3’UTR of Bcl2, miR-190b induces osteosarcoma cell apoptosis and confers radio-sensitivity to gastric cancer cells ( 58 , 59 ). According to reports, BCL11A acts as a carcinogenic gene for a variety of human cancers, such as breast cancer ( 60 ), laryngeal squamous cell carcinoma ( 61 ), high-risk neuroblastoma ( 62 ), non-small cell lung cancer ( 63 ) etc. In addition, the expression of PSMG3-AS1 in breast cancer tumor tissues and cell lines was increased, and PSMG3-AS1 as a sponge of miR-143-3p enhanced the proliferation and migration ability in the pathogenesis of breast cancer ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, by directly interacting with the 3’UTR of Bcl2, miR-190b induces osteosarcoma cell apoptosis and confers radio-sensitivity to gastric cancer cells ( 58 , 59 ). According to reports, BCL11A acts as a carcinogenic gene for a variety of human cancers, such as breast cancer ( 60 ), laryngeal squamous cell carcinoma ( 61 ), high-risk neuroblastoma ( 62 ), non-small cell lung cancer ( 63 ) etc. In addition, the expression of PSMG3-AS1 in breast cancer tumor tissues and cell lines was increased, and PSMG3-AS1 as a sponge of miR-143-3p enhanced the proliferation and migration ability in the pathogenesis of breast cancer ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…LSCC is characterized by local recurrences, lymph node metastasis and poor sensitivity to chemotherapeutic drugs, which severely restricts the effects of LSCC treatment [ 2 , 27 ]. Autophagy plays critical roles in regulation of invasion, metastasis, and chemosensitivity in various type of cancers [ 28 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of screening, the ROC curve showed that the risk score calculated according to the signature was the best measure for determining the survival of patients with LSCC, with a higher area under the curve than any clinical parameter (age, sex, neoplasm histologic grade, stage, tumor stage, node stage; Figure 6A ) and any single gene included in the IRDEG signature ( Figure 6B ). Moreover, we also compared the performance of the signature to potential markers related to the prognosis of LSCC identified in research recently added to PubMed (published between January 1, 2020 and May 15, 2020), while 9 of the potential markers – activated leukocyte cell adhesion molecular ( ALCAM ) [ 39 ], ATM [ 40 ], BAF chromatin remodeling complex subunit ( BCL11A ) [ 41 ], B-cell lymphoma 2 ( BCL-2 ) [ 42 ], desmoglein 2 ( DSG2 ) [ 43 ], epidermal growth factor receptor ( EGFR ) [ 44 ], FGFR1 [ 45 ], homeobox A13 ( HOXA13 ) [ 46 ], insulin like growth factor 1 receptor ( IGF-1R ) [ 47 ] – were included in the RNA-Seq data used in this study. Compared with any gene from these 9 potential prognostic markers, the risk score based on the IRDEG signature showed the best ability to screen for prognosis in patients with LSCC ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of screening, according to the ROC curves, the risk score calculated for the signature proved better at predicting the prognosis of patients with LSCC than any single parameter including age, sex, neoplasm histologic grade, stage, or tumor or node stage, as well as any single IRDEG used to create the signature. Moreover, the risk score also was better for screening and predicting prognosis than any of the recently reported prognostic markers for LSCC, namely, ALCAM [ 39 ], ATM [ 40 ], BCL11A [ 41 ], BCL-2 [ 42 ], DSG2 [ 43 ], EGFR [ 44 ], FGFR1 [ 45 ], HOXA13 [ 46 ], and IGF-1R [ 47 ]. In terms of prognosis, not only was the OS rate in the high-risk score group significantly lower than in low-risk score group, but the risk curve showed that there were significantly fewer deaths in patients with lower risk scores.…”
Section: Discussionmentioning
confidence: 99%